Dari Sungai Kampar Ke Candi Muara Takus: Menelusuri Nilai Kebangsaan Dalam Warisan Sejarah Melayu Riau - Aura Rabi'ah Zaukhan, Arilianti; ali, Hamb; Rahmadani, Nehya; Asti Indriani, Silvia; Alpiyanti, Zaskiya (Universitas Muhammadiyah Ponorogo, 2026)
This study aims to analyze the national values present in the historical and cultural heritage of the Muara Takus Temple in Kampar Regency, Riau Province, as well as their relevance as a learning resource for Civic Education. The research focuses on the forms of national values that are alive in the social practices of communities around the temple. This study employs a field research method with a qualitative approach. Data were collected through observation, semi-structured interviews with site managers and local residents, and documentation. Data analysis was conducted descriptively using qualitative techniques through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the transformation of the Muara Takus Temple from a religious site to a religious and cultural tourism area has strengthened values such as mutual cooperation (gotong royong), unity, patriotism, and historical awareness among the community. These values align with the objectives of Civic Education in shaping citizens with a national identity and a sense of nationalism. Therefore, the Muara Takus Temple has the potential to be utilized as a contextual learning resource in Civic Education, particularly for secondary school students.